The temptation of luck: The Machiavellian prince and the Hobbesian sovereign facing moral and honour-motivated responsibilities. (June 2022) - Untea, Ionut
In political philosophy, brute or circumstantial luck entails responsibilities. Even so, leaders may be tempted to capitalize on lucky endowments or circumstances that turn in their favour without giving too much attention to moral responsibility. This is because besides moral responsibility, there is another kind of responsibility that flows out of luck. Machiavelli and Hobbes provide the classic philosophical accounts of honour-based responsibility and universal moral responsibility. While this distinction is only suggested by Machiavelli, Hobbes explicitly develops an account of the laws of honour and the laws of nature that make the essential difference between a political community and a community where the state of war becomes less visible, although still ongoing.